Reliability and validity of a soccer-specific test of prolonged repeated-sprint Ability - Oliver, J. L.; Armstrong, N.; Williams, C. A. (International Journal of Sports Physiology and Performance, 2007)
The purpose of the study was to assess the reliability and validity of a newly developed laboratory protocol to measure prolonged repeated-sprint ability (RSA) during soccer-specific exercise. Methods: To assess reliability, 12 youth soccer players age 15.2 ± 0.3 y performed 2 trials of a soccer-specific intermittent-exercise test (SSIET) separated by 3 months. The test was performed on a nonmotorized treadmill. A separate sample of 12 youth soccer players (15.2 ± 0.3 y) completed the SSIET while simultaneously HR, VO2, and blood lactate (BLa) were monitored. The SSIET was designed to replicate the demands of competing in one half of a soccer match while sprint performance was monitored. The test included a 5-s sprint every 2 min. Results: The mean coefficient of variation was 2.5% for the total distance covered during the SSIET and 3.8% for the total distance sprinted; measures of power output were less reliable (=5.9%). Participants covered 4851 ± 251 m during the SSIET, working at an average intensity of 87.5% ± 3.2% HRpeak and 70.2% ± 3.1% VO2peak, with ~7mmol/L BLa accumulation. A significant reduction (P < .05) in sprint performance was observed over the course of the SSIET. Conclusion: The SSIET provided a reliable method of assessing prolonged RSA in the laboratory. The distance covered and the physiological responses during the SSIET successfully recreated the demands of competing in a soccer match.